Establishing the Market Potential of a Rental Model Multipurpose Electric Vehicle (MPEV) for Individuals with Lower Limb Disabilities in India - Veena, A.; D’Souza, Daxon (Indian Journal of Marketing, 2017)
Electric vehicles (EV) were developed as a sustainable and cost-effective solution to the environmental problems resulting from petroleum-based forms of transportation. In recent years, renting of vehicle systems has garnered a great deal of interest and activity internationally as an innovative transportation solution. Existing research about EVs is largely concentrated on a purchase model. Results included perceptions of high costs to purchase and maintain EVs. This study, in contrast, focused on a rental model of EVs offering the potential to lower transportation costs and cost-sustainable option. The objective also included understanding the users’ perception of a potential rental model of electric vehicles (EV). The study used the survey method to assess the perception, potential benefits, and drawbacks of a rental model of EVs. The expected findings included positive perceptions of the cost savings associated with the EV rental model versus the hybrid rental model.